Bahaya Higher Criticism terhadap Ineransi Alkitab dalam Kehidupan Orang Percaya Masa Kini - Benaya Dwi Cahyono; Suhadi Suhadi (Jurnal Teologi Berita Hidup, 2024)
The teaching of the inerrancy of the Bible is important for all believers to understand because it relates to the foundation for the Christian faith. The Bible is a reference for believers in making decisions when facing doubts about Faith. If the foundation is not strong, it can be ascertained that there is a wrong decision making. Rejecting the doctrine of inerrancy can result in the denial of other Christian doctrines. The problem that occurs is the rejection of the innocence of the Bible, especially among the Higher Criticism. But the existence of the Bible is still recognized and believed by Christians today. In understanding this writing, quantitative methods are used with literature studies by examining various representative sources related to the issue of inerrancy based on the Higher Criticism’s view of the Inerrancy of the Bible.